Surface Velocities and Strain-Rates in the Euro-Mediterranean Region From Massive GPS Data Processing - Enrico Serpelloni; Enrico Serpelloni; Adriano Cavaliere; Leonardo Martelli; Francesco Pintori; Letizia Anderlini; Alessandra Borghi; Daniele Randazzo; Daniele Randazzo; Sergio Bruni; Roberto Devoti; Paolo Perfetti; et al. (Frontiers in Earth Science, 2022)
In this work we present and discuss new geodetic velocity and strain-rate fields for the Euro-Mediterranean region obtained from the analysis of continuous GNSS stations. We describe the procedures and methods adopted to analyze raw GPS observations from >4000 stations operating in the Euro-Mediterranean, Eurasian and African regions. The goal of this massive analysis is the monitoring of Earth’s crust deformation in response to tectonic processes, including plate- and micro-plate kinematics, geodynamics, active tectonics, earthquake-cycle, but also the study of a wide range of geophysical processes, natural and anthropogenic subsidence, sea-level changes, and hydrology. We describe the computational infrastructure, the methods and procedures adopted to obtain a three-dimensional GPS velocity field, which is used to obtain spatial velocity gradients and horizontal strain-rates. We then focus on the Euro-Mediterranean region, where we discuss the horizontal and vertical velocities, and spatial velocity gradients, obtained from stations that have time-series lengths longer than 6 and 7 years, which are found to be the minimum spans to provide stable and reliable velocity estimates in the horizontal and vertical components, respectively. We compute the horizontal strain-rate field and discuss deformation patterns and kinematics along the major seismogenic belts of the Nubia-Eurasia plate boundary zone in the Mediterranean region. The distribution and density of continuous GNSS stations in our geodetic solution allow us to estimate the strain-rate field at a spatial scale of ∼27 km over a large part of southern Europe, with the exclusion of the Dinaric mountains and Balkans.